LIVER DAMAGE IN PSORIASIS AND PSORIATIC ARTHRITIS: A LITERATURE REVIEW - Yu. L. Korsakova; T. V. Korotaeva (Научно-практическая ревматология, 2017)
Psoriasis (Ps) is a chronic systemic disease that affects the skin. Investigation could reveal the high prevalence of nonalcoholic fatty liver disease (NAFLD) in patients with Ps compared with the general population, especially in those who have moderate to severe Ps with a high Ps area severity index (PASI). Similar pathogenic processes play a definite role in this relationship. The most likely causes are recognized to be insulin resistance and elevated levels of proinflammatory cytokines. According to recent evidence, the prevalence of NAFLD and metabolic syndrome in patients with Ps is higher than that in the general population. In addition, patients with NAFLD and Ps are at higher risk of severe liver fibrosis than those with NAFLD without Ps. Therapy for this condition certainly needs not only to modify traditional risk factors, but also to reliably suppress inflammation. Obesity and NAFLD have a negative impact on the results of treatment in patients with psoriatic arthritis with biological agents.